Code Switching Found in the Conversation between Bunga Citra Lestari and Daniel Mananta on “It’s Me BCL” YouTube Channel - Ni Komang Sri Ayu Laksmi; I.G.B. Wahyu Nugraha Putra; Putu Devi Maharani (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2023)
This study concerned the types and reasons of code-switching on three videos between Bunga Citra Lestari and Daniel Mananta’s conversation. The data source were taken from Bunga Citra Lestari’s YouTube channel entitled “IT’S ME BCL”. The data analysis was conducted a descriptive qualitative method. This study showed 3 types of code switching that found in the findings by applying Poplack’s theory (1980) as cited in Romaine (1989). Those types included intra-sentential switching, tag switching, and inter-sentential switching. The most type of code switching that dominantly occurred in this study namely intra-sentential switching. Those were appeared along the conversation between Bunga Citra Lestari and Daniel Mananta which aimed to convey the motivations through words, clauses, and phrases that were comfortable to be conducted in the second language. Moreover, this study also focused on the reasons of code switching by applying the theory proposed by Hoffman (1991). Those reasons could be divided into talking about certain things, quoting somebody else, showing empathy, using interjection, repeating something, clarifying the speech, and expressing group identity. The most reason of code-switching that dominantly occurred between Bunga Citra Lestari and Daniel Mananta’s conversation was talking about certain things. Those were occurred during the role of Daniel Mananta who was being an interviewer was asking several questions to Bunga Citra Lestari who was being an interviewee that automatically built up their conversation.